Uma política de educação em ciência - Branquinho, Fatima Teresa Braga (1992)
The analysis of an educational experience started from a pact betiween Universidade do Estado do Rio de Janeiro (UERJ) and Fundação Osvaldo Cruz (FIOCRUZ) permitted the formulation of an educational policy toward the improvement of the graduation in Sciences. basic The worry with the topic is justified due to the nowadays scientific societies establish a requirement to the people understand and participate of the discussions that determine the ways gotten by these societies: to Know Sciences. The cibernetic and the cognition sciences, roots of the last Scientific Revolution, gave up the holographic paradigm to base the conception of education used as principIe to the policy formulated.